THE RELATIONSHIP BETWEEN WOMEN’S LABOR FORCE PARTICIPATION AND ECONOMIC GROWTH: PANEL DATA ANALYSIS FOR COUNTRY GROUPS (Third Sector Social Economic Review, 2019)
Women are an important part of the manpower involved in the economic growth of a society. Women in most of the countries are underrepresented in the labour force. In this regard, the equity and efficiency related Sustainable Development Goals, in particular; ensuring inclusive and equitable quality education and promote lifelong learning opportunities; achieving gender equality and empower all women; promoting sustained economic growth have become desirable goals and target for policy formulation. In this study, the presence of U shaped relationship between female labor force participation rate and economic growth is investigated by panel data anaysis for 48 high income countries, 46 upper-middle income countries, 41 lower-middle income countries and 27 low income countries  using World Bank data set between 1996 and 2017.
Keywords: Female Labor Force Participation; Economic Growth; U-shaped Feminisation Hypothesis; Panel Data Analysis